Patterns of distribution and abundance of Greater Snow Geese on Bylot Island, Nunavut, Canada 1983-1998 - Reed, A.; Hughes, R. J.; Boyd, H. (Wildfowl, 2014)
To monitor the numbers and distribution of Greater Snow Geese at the largest breeding colony in the eastern Canadian High Arctic, surveys were conducted on Bylot Island at five year intervals from 1983 to 1998.